Adoption and Utilization of Business Innovations of Agricultural Research in Uganda: Empirical Analysis. - Barekye, Alex; Tamwesigire, Caleb (Kabale University, 2024)
This paper seeks to examine the adoption of business innovations within the context of the agricultural sector in Uganda. The findings emerge from research carried out to assess the utilization of business innovations of research in Uganda considering the National Agricultural Research Organization(NARO) as a reference, specifically to find out the association between innovation attributes and their use on-farm, as well as establish the consequence of innovation features and demand (market) about the use of discoveries in farm management. The opinions of 99 participants in producing major crops in the Kanungu district where the NARO innovations were verified were sought. The information was assembled and scrutinized with SPSS and STATA. The findings revealed that innovation features played an important role in the extent of application of the technology. Similarly, how old participants have had a negative linkage with the use of technologies, while the extent of education helps the application of technologies by farmers.